An in vitro Assessment of The Effectiveness of Some Bactericides on Bacteria Isolated from Soaking Float - Nail Yapici, Ali; Mericli Yapici, Binnur; Karaboz, Ismail; Tozan, Murat (Asian Journal of Chemistry, 2010)
In this study, the effectiveness of 5 commercial bactericides commonly used in leather processing was examined in vitro. Bacteria were isolated from soak water by means of proteolytic bacteria culture medium, plate count agar (PCA) and halotolerant bacteria medium containing 10 % NaCl and identified as Gram positive Staphylacoccus sp., Diplococcus sp., Micrococcus sp., Corynobacterium sp., Bacillus sp. and Gram negative bacterium. The effectiveness of bactericides was determined in vitro on these bacteria through disc diffusion method. Results were evaluated in comparison with antimicrobial activities of some standard antibiotics on the same microorganisms. It was observed that Derbio DB 99® (bactericide I) was effective on all types of bacteria. Biocide B-7® (bactericide II) was effective on Staphylacoccus sp., Diplococcus sp. and Micrococcus sp. It was also observed that Aracit KL® (bactericides III) and Preventol Z-L® (bactericides IV) were effective only against Staphylacoccus sp. and Diplococcus sp. On the other hand, Pluscide HP® (bactericides V) did not show enough effectiveness. As a result, it was found out that the most effective bactericide was Bactericide I.